The future of artificial intelligence in gerontological nursing in Saudi Arabia - Noura Almadani (BMC Geriatrics)
Abstract Background As a part of Vision 2030, Saudi Arabia initiated a health transformation program to enhance the quality and efficiency of healthcare services through digitizing the health sector and introducing various technological innovations. Methods A qualitative approach was used to explore the future of artificial intelligence (AI) of eight postgraduate students in the gerontological nursing program by investigating their perceptions, experiences, and challenges. The data was presented as key themes and subthemes using thematic analysis methods. Results The thematic analysis revealed the precise role of AI in gerontological nursing. While participants strongly believe that AI has the potential to improve patient care and nursing efficiency, they also expressed significant concerns regarding ethical implications. Conclusions The research highlights that AI is pivotal in developing healthcare solutions for older adults. By automating routine tasks and offering personalized medical and social interactions, AI can potentially transform gerontological nursing practices.